SIRIA Y LAS NORMAS DE DERECHO INTERNACIONAL SOBRE ARMAS QUÍMICAS: ¿UNA SOLUCION AL CONFLICTO? - Bautista Hernáez, Andrés (2014)
The attention of the internationalcommunity has been recently beenfocused on an unprecedented fact:Syria’s accession to the 1993 Conventionon Chemical Weapons.This rule represents a qualitativeadvance on the prohibition regimeconcerning chemical weapons. Thispaper analyzes the type of rules andprinciples which prohibits chemicalweapons and their applicability onSyria. Furthermore we will focus insome possibilities to solve the Syriancrisis, in particular by the latest SecurityCouncil Resolution 2118.